Socioeconomic assessment of adoption of production and processing technologies on farming households in Nigeria - Ayedun, B.; Okuneye, P.A.; Dipeolu, A.; Abdoulaye, Tahirou (2013)
The study examined 'Socioeconomic assessment of adoption of production and processing technologies on farming households'. Using multistage sampling techniques, 480 farming households from Intervention villages - IVs and the Non-Intervention villages - NIVs were sampled from South Zones of Nigeria and interviewed. Targeted respondents were interviewed with the aid of questionnaires. This study was carried out to provide credible evidence of the impact of IITA-ICP (International Institute of Tropical Agriculture, Integrated Cassava Project) research on cassava incited by cassava presidential initiative ' (PI) of 2002 in Nigeria and to draw lessons from these interventions. Using descriptive and econometric tools, the result showed that cassava occupies 43% of the total field cultivated for crops. Awareness and adoption of production and processing technology were generally poor: for production technology, it was highest for improved cassava sett both in awareness (87%) and adoption (68%) and IVs took the lead. In processing technology among households, grating machine had the highest awareness (88%) and adoption rate (78%) followed by pressing machine. In many cases, intervention households and enterprises had better awareness and adoption rates. Poverty status estimation revealed that less people were below poverty lines among adopters compared to non-adopters, and among IVs compared to counterfactuals. Using logit model, variables that had poverty reducing effect included 'being from intervention villages, adoption of grater machine for processing cassava, having non-farm income, and being educated